Biological activities of ophiobolin K and 6-epi-ophiobolin K produced by the endophytic fungus Aspergillus calidoustus. Issue 4 (16th February 2016) - Rodrigues de Carvalho, Camila; Vieira, Mariana de Lourdes Almeida; Cantrell, Charles L.; Wedge, David E.; Alves, Tânia M.A.; Zani, Carlos Leomar; Pimenta, Raphael Sanzio; Sales Junior, Policarpo A.; Murta, Silvane M.F.; Romanha, Alvaro J.; Rosa, Carlos Augusto; Rosa, Luiz H.
Abstract : Endophytic fungi represent ubiquitous microbial organisms able to live in the tissues of different plants around the world and represent a prolific source of bioactive metabolites. In the present study, the endophytic fungus Aspergillus calidoustus was isolated from the medicinal plant Acanthospermum australe ( Asteraceae ), and identified using molecular, physiological and morphological methods. A methylene chloride crude extract of A. calidoustus has been produced and subjected to antifungal bioassay-directed fractionation which resulted in the isolation of the two bioactive compounds: ophiobolin K and 6-epi-ophiobolin K. These pure compounds displayed antifungal activity against fungal plant pathogens, protozoal activity against Trypanosoma cruzi, and cytotoxic activity against human tumoral cell lines. The results show that A. calidoustus was able to produce the antifungal and cytotoxic metabolites ophiobolin K and 6-epi-ophiobolin K, which may help the fungus to colonise and occupy the substratum as well as survive in natural environments. Abstract :